2003
DOI: 10.1590/s0102-311x2003000700005
|View full text |Cite
|
Sign up to set email alerts
|

Reflexões sobre a amamentação no Brasil: de como passamos a 10 meses de duração

Abstract: In 1975, one out of two Brazilian women only breastfed until the second or third month; in a survey from 1999, one out of two breastfed for 10 months. This increase over the course of 25 years can be viewed as a success, but it also shows that many activities could be better organized, coordinated, and corrected when errors occur. Various relevant decisions have been made by international health agencies during this period, in addition to studies on breastfeeding that have reoriented practice. We propose to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
129

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(186 citation statements)
references
References 15 publications
4
53
0
129
Order By: Relevance
“…In 1991, the Baby Friendly Hospital Initiative (BFHI) was implemented, with the aim of changing the maternity ward routines in order to comply with the Ten Steps to Successful Breastfeeding. [18][19][20][21] Step 2 suggests that the whole healthcare staff who assist mothers and infants should be properly trained in the clinical management of breastfeeding. This is achieved by means of courses that highlight the importance of breastfeeding assessment through a specific protocol (form for observation and assessment of breastfeedings), including the observation of mother and infant positioning, infant responses (global behavior), mother and infant bonding, anatomy of the breast, aspects related to suction, and oral functioning.…”
Section: Breastfeeding Assessmentmentioning
confidence: 99%
“…In 1991, the Baby Friendly Hospital Initiative (BFHI) was implemented, with the aim of changing the maternity ward routines in order to comply with the Ten Steps to Successful Breastfeeding. [18][19][20][21] Step 2 suggests that the whole healthcare staff who assist mothers and infants should be properly trained in the clinical management of breastfeeding. This is achieved by means of courses that highlight the importance of breastfeeding assessment through a specific protocol (form for observation and assessment of breastfeedings), including the observation of mother and infant positioning, infant responses (global behavior), mother and infant bonding, anatomy of the breast, aspects related to suction, and oral functioning.…”
Section: Breastfeeding Assessmentmentioning
confidence: 99%
“…A tendência crescente dessa prática pode ser explicada, pelo menos em parte, pela implementação de várias políticas públicas pautadas no Programa Nacional de Incentivo ao Aleitamento Materno em 1981 5 . Destacam-se a expansão da Rede Brasileira de Bancos de Leite Humano (Rede BLH) e da Iniciativa Hospital Amigo da Criança (IHAC), os avanços na regulamentação da Norma Brasileira de Comercialização de Alimentos para Lactentes e Crianças de Primeira Infância, Bicos, Chupetas e Mamadeiras (NBCAL), além da mobilização social provocada pela comemoração anual da Semana Mundial da Amamentação 6 .…”
unclassified
“…2 Nevertheless, we were able to perceive that, during the interviewees' childhood, at home and/or at school, the conversations they had about breastfeeding and the guidance they received were neither consistent nor substantiated. This is demonstrated by the fact that their speech revealed ambiguous or faded memories: one moment they couldn't remember anything; the next they were breastfed or given milk other than their mothers'; one moment the school discussed the subject; the next, breastfeeding wasn't mentioned.…”
Section: Resultsmentioning
confidence: 83%
“…2,3 The causes of this situation may originate in the experience that breastfeeding is seen merely as a technique, without taking into consideration the historical, social and cultural context, or the fact that this is a process that involves feelings and emotions. 4,5 Studies have indicated that the participation of the father is important to the success of this practice.…”
Section: Introductionmentioning
confidence: 99%